Detection of ochratoxin A in human breast milk in Jiroft city, south of Iran - Ali Kamali; Sareh Mehni; Mohadeseh Kamali; Mehdi Taheri Sarvtin (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Breastfeeding plays an important role in the growth and development of infants. However, breast milk may be contaminated with various mycotoxins. Ochratoxin A is one of the most important mycotoxins with nephrotoxic, carcinogenic, teratogenic, genotoxic, and immunotoxic properties. Thus, we carried out this study to determine the concentration of ochratoxin A in human breast milk in Jiroft, Kerman Province, south of Iran. Materials and Methods: Eighty-four human breast milk samples were collected from mothers visiting the number one clinic in Jiroft city. Enzyme-linked immunosorbent assay (ELISA) was used to detect ochratoxin A in the samples. Results: Ochratoxin A was found in all the tested samples at a concentration ranging from 0.11 to 7.34 ng/ml. The mean concentration of ochratoxin A in the samples was 1.99±1.34 ng/ml. Fourteen samples contained ochratoxin A at concentrations exceeding the quantitation limit (3 ng/ml). Conclusion: The results of this study showed that infants are exposed to ochratoxin A in our region. In cases exceeding the quantitation limit, the infant's body cannot detoxify the toxin. Therefore, the infant can be affected by various illnesses such as nephropathy, immune system deficiency, and different types of cancer.